Community Participation in Controlling Pollution and Damage to the Citarum River Watershed in Binong Village, Bandung City - Dewi Loka Wardiya Ningsih; Marsha Radhia Ananda (Social Impact Journal, 2023)
This study analyzes the participation of the people of Binong Village, Bandung City, in the implementation of the Acceleration of Pollution Control and Damage to the Citarum River Basin. With a qualitative approach and case studies involving residents affected by eviction as a population, Data collection methods involve interviews, direct observation, and document analysis. The success of the Citarum Harum program, based on Presidential Regulation Number 15 of 2018, requires community participation. The establishment of a forum between RWs in Binong Village as a forum for community aspirations. Despite the stimulant relief, some residents were disappointed that compensation was not comparable. The ability of communities to be involved in the decision process varies, with some supporting river revitalization while others contradicting the lack of clarity about relocation for longstanding residents. The decision-making process is considered less involving the community, with socialization only including regulatory information without considering the real condition of the population. This study provides a comprehensive overview of community participation in pollution control policies in the Citarum watershed, emphasizing the importance of considering community perspectives in environmental policy planning.